Examining key stakeholder’s neglect as an obstacle to effective administrative reform in the Nigerian power sector / Ashiru Olayemi Aliyu, Kuppusamy Singaravelloo and Norma Mansor - Ashiru, Olayemi Aliyu; Singaravelloo, Kuppusamy; Mansor, Norma (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Scholars have long recognized a stable electricity supply as a critical infrastructure required to facilitate economic growth and development in all nations. But, despite concerted efforts made by the successive governments in Nigeria to rejig the power sector for optimal performance. No substantial progress has been achieved; the initiatives have over time produced unintended outcomes. Thus, this study examines issues ascribed to the unintended outcomes against the anticipated result. In this article, a survey research method, a cross-section study, and a purposive sampling technique were adopted. The study distributed a total of 463 closed-ended questionnaires where 401 were returned to establish the complex relationship between the dependent and independent variables. Data obtained was analysed using WarpPLS software, a variance-based Structural Equation Model. The study found that stakeholder support, which is required to drive a purposeful reform exercise, was conspicuously lacking. The research suggests a strong alignment, collaboration, and cooperation amongst the stakeholders as a necessity and a sine qua non to purposeful reform outcome.